Molar incisor hypomineralization: considerations about treatment in a controlled longitudinal case - Oliveira, Daniela Cristina de [UNESP]; Favretto, Carla Oliveira [UNESP]; Cunha, Robson Frederico [UNESP] (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2015)
Molar incisor hypomineralization (MIH) is a defect in the tooth enamel of systemic origin and may affect one or all four first permanent molars frequently associated with the permanent incisors. This case reports a 7-year-old child with severe MIH in the permanent molars associated with tooth decay and intense pain. In the first stage of treatment, therapy was performed with fluoride varnish and restoration with glass ionomer cement (GIC). After 6 years of clinical and radiographic follow-up, the restorations presented wear and fractures on the margins, indicating their replacement with composite resin. Severe cases of MIH in the early permanent molars can be treated with varnish and GIC to restore the patient's comfort and strengthen the hypomineralized dental structures. The clinical and radiographic monitoring frequently indicated when the restoration with composite resin should be performed.